First Documented Record of Progne subis (Hirundinidae) from Rio Grande do Norte State, Brazil - Souto, Glauber Henrique Borges de Oliveira; Pequeno, José Arthur Felipe; Santos, Vanessa Kayane Medeiros; Grangeiro, Raissa Danielle Praxedes (Brazilian Journal of Science, 2025)
We report the first confirmed record of the Purple Martin (Progne subis Linnaeus, 1758) for the state of Rio Grande do Norte, Brazil. The record was obtained on 19 February 2025 in the municipality of Lajes/RN, located in the Central Potiguar mesoregion, where the Caatinga biome predominates. This finding represents a significant addition to the avifauna of Rio Grande do Norte, as it expands the known distribution of the species in northeastern Brazil. The confirmation of its occurrence in Lajes contributes to updating the state bird checklist and may support future surveys aimed at detecting additional regional populations.